Risk of cardiovascular disease outcomes in primary care subjects with familial hypercholesterolaemia: A cohort study. (August 2019) - Iyen, Barbara; Qureshi, Nadeem; Kai, Joe; Akyea, Ralph K.; Leonardi-Bee, Jo; Roderick, Paul; Humphries, Steve E.; Weng, Stephen
Abstract: Background and aims: Familial hypercholesterolaemia (FH) is a known major cause of premature heart disease. However, the risks of atherosclerotic disease in other vascular regions are less known. We determined the risk of major cardiovascular disease (CVD) outcomes associated with clinical FH. Methods: In a retrospective cohort study (1 January, 1999 to 22 July, 2016), we randomly-matched 14, 097 UK subjects with clinical FH diagnoses or characteristics (Simon-Broome definite or Dutch Lipid Clinic Score >8) to 42, 506 subjects without FH by age, sex, general practice. We excluded those with CVD at baseline. Incident rates for coronary heart disease (CHD), stroke or transient ischaemic attack (TIA) and peripheral vascular disease (PVD) were estimated. Cox proportional hazards regression, stratified on matched-pairs, determined adjusted hazards ratios (HR) for incident CVD. Results: During follow-up (median 13.8 years), incidence rates (95% CI) of CVD (per 1000 person-years) were 25.6 (24.8–26.3) in FH and 2.9 (2.8–3.1) in non-FH subjects. The risk of CHD, stroke/TIA and PVD was higher in FH compared to non-FH subjects: CHD (HR 10.63, 95% CI 9.82–11.49), stroke/TIA (HR 6.74, 95% CI 5.84–7.77), PVD (HR 7.17, 95% CI 6.08–8.46). The risk of CVD was greater in those with FH characteristics (HR 13.52, 95% CI 12.48–14.65) than those with clinical diagnoses (HR 1.66, 95% CI 1.42–1.93). Conclusions: In addition to the recognised increased risk of CHD, subjects with FH have greatly elevated risk of stroke/TIA and PVD. This emphasises need for early diagnosis and preventive interventions beyond CHD, to reduce CVD risk in these individuals. Graphical abstract: Image 1 Highlights: Subjects with clinical FH had elevated risks of stroke/TIA and PVD in addition to theraised risk of coronary heart disease. Undiagnosed FH subjects had much greater risks of all CVD outcomes than subjects with clinical FH diagnosis. Only 75% of the FH subjects were on lipid-lowering treatment, and only 38% of those on treatment were on high-potency statins.